1998
DOI: 10.1021/js980175v
|View full text |Cite
|
Sign up to set email alerts
|

Tween protects recombinant human growth hormone against agitation-induced damage via hydrophobic interactions

Abstract: In the absence of surfactants, recombinant human growth hormone (rhGH) rapidly forms insoluble aggregates during agitation. The nonionic surfactant Tween 20, when present at Tween:protein molar ratios >4, effectively inhibits this aggregation. Differential scanning calorimetry (DSC) of rhGH solutions showed melting transitions that decreased by ca. 2 degrees C in the presence of Tween. Circular dichroism (CD) studies of the same thermal transition showed that the decrease is specific to the relatively high pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
180
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(196 citation statements)
references
References 25 publications
14
180
0
2
Order By: Relevance
“…A further mechanism, often presented, considers a direct interaction and binding of the detergent with the protein [30,[37][38][39]. It is discussed that such a binding is especially observed for proteins having hydrophobic amino acid residues close to the water interface.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A further mechanism, often presented, considers a direct interaction and binding of the detergent with the protein [30,[37][38][39]. It is discussed that such a binding is especially observed for proteins having hydrophobic amino acid residues close to the water interface.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…When emulsions are prepared, the total interfacial area increases as the droplet size decreases but it was observed that the exposure to the oil-water interface combined with the mechanical stress of manufacture is not quite as harsh a treatment as simple shaking and exposure to the air-solution interface (Jorgensen et al, 2003). Furthermore, a better protection of the protein from exposure to interfaces may be obtained by addition of surfactants due either to a steric effect which blocks aggregation-prone hydrophobic sites on the protein surface (Bam et al, 1998) or to a competitive effect with the protein for space at the surface, thereby, preventing part of the protein from reaching the interface and the subsequent adsorption and structural perturbation (Jorgensen et al, 2004). This may explain the preservation of insulin stability during microspheres preparation, suggesting that emulsification/internal gelation is appropriate for the encapsulation of proteins.…”
Section: Bioactivitymentioning
confidence: 99%
“…Several mechanisms for protein stabilization by surfactants have been reported in the literature. Nonionic surfactants can protect proteins against surface-induced aggregation by competing with proteins for adsorption sites on surfaces, by binding to hydrophobic regions on the protein surface and thereby decreasing intermolecular interactions (8)(9)(10)(11), by increasing the free energy of protein unfolding (12), and finally, nonionic surfactants may act as chemical chaperone, favoring refolding over aggregation by binding transiently with partially folded protein molecules and sterically hindering intermolecular interactions that result in aggregation (13,14). Surfactants can also modulate adsorption loss and aggregation by coating interfaces and/or participating in protein-surfactant associations as demonstrated by Lee et al (15).…”
Section: Introductionmentioning
confidence: 99%